History textbooks and the formation of the image of the nation - Puerta Villagaray, César (2022)
The article seeks to understand if history textbooks are still instruments that contribute to the process of image formation about the Peruvian nation. The central argument points out that in recent decades history textbooks are conceived as resources for the pedagogical implementation of a more pluralistic conception of the nation, more attentive to social and cultural diversity. The work is divided in three parts. In the first, one reflects on the school textbook as an object of study. In the second, it is explained how school texts played an important role in the formation of the imaginary about the nation. In the third part, two themes of history are examined, independence (first decades of the 19th century) and the years of political violence (1980-2000), in secondary school textbooks for the year 2012.